Identification of Project Based Learning and STEM PjBL Innovation Based on Socio Scientific Issues as an Effort to Improve Students' Scientific Literacy - Evita Anggereini*; Jodion Siburian; Afreni Hamidah (Jurnal Pendidikan Sains Indonesia, 2023)
Socio scientific issues deals with learning materials related to controversial issues that develop along with the development of scientific and technological advances.This study aims to compare the PjBL learning model with the STEM PjBL learning model based on socio scientific issues in each class in the biology education study program in improving students' scientific literacy. Quantitative research methods are associative and comparative types. This study took research samples from the research population, namely students in the 7th semester of the biology education study program as many as 60 samples. The sampling technique uses simple random sampling. Data collection used a student response questionnaire to the PjBL learning model and a scientific literacy questionnaire. The results of the t test found that there were differences in the responses of regular students A and regular B to the PjBL learning model and the STEM project based learning innovation based on SSI learning model. The results of the correlation test found that there was a significant relationship between the responses of regular B semester 7 biology education students to the PjBL model variables and students' scientific literacy